Patterns and short term neurosurgical treatment outcomes of neonates with neural tube defects admitted to Felege Hiwot Specialized Hospital, Bahir Dar, Ethiopia - Yohannes Addisu; Gizachew Tadesse Wassie (BMC, 2024)
Abstract Background Neural tube defects (NTDs) account for the largest proportion of congenital anomalies of the central nervous system and result from failure of the neural tube to close spontaneously between the 3rd and 4th weeks of in utero development. Prognosis and treatment outcome depends on the nature and the pattern of the defect. The nature of treatment outcomes and its pattern associated with grave prognosis is not well known in the study area. Objective The aim of study was to determine the patterns and short term neurosurgical management outcomes of newborns with neural tube defects admitted at Felege Hiwot Specialized Hospital. Methods Institutional based retrospective cross-sectional study among neonates, who were admitted at Felege Hiwot Specialized Hospital with neural tube defects from January 1st to December, 30th, 2018 was conducted. All Charts of Neonates with confirmed diagnosis of neural tube defects were included as part of the study. Trained data collectors (medical interns) supervised by trained supervisors (general practitioners) collected the data using a pretested data extraction format. Data were coded, entered and analyzed using SPSS version 23 software. Frequency and cross tabulations were used to summarize descriptive statistics of data, and tables and graphs were used for data presentation. Result About 109 patients had complete documentation and imaging confirmed neural tube defects. Myelomeningocele was the commonest pattern 70 (64.2%). Thoracolumbar spine was the commonest site of presentation 49(45%). The most common associated impairment was hydrocephalus 37(33.9%). Forty-five (41.1%) had multiple complications. The mortality rate was 7.3%, 44% were discharged with sequalae and 36.7% were discharged without impairment. The significant causes of death were infection 66.7% and Chiari crisis 33.3%. Conclusion Myelomeningocele was the most frequent clinical pattern of neural tube defect and thoracolumbar spine was the commonest site. Isolated neural tube defect was the commonest finding. There were multiple complications after surgery accompanied with meningitis and hydrocephalus. The mortality rate among neonates with neural tube defects was considerably high. The commonest causes of death were infection and Chiari crisis.